Sociodemographic and behavioural risk factors associated with low awareness of diabetes mellitus medication in Indonesia: Findings from the Indonesian Family Life Survey (IFLS-5) - Khoiry, Qisty A.; Alfian, Sofa D.; Abdulah, Rizky (Frontiers in Public Health, 2023)
Introduction Low awareness of the necessity of taking medication is common among patients with diabetes mellitus (DM) due to their lack of understanding of the disease. Therefore, it is essential to determine the underlying risks influencing low awareness to design effective intervention strategies. This study aims to evaluate the association of sociodemographic and behavioural factors with low awareness to take medication among patients with DM in Indonesia. Method Retrospective data were obtained from the Indonesian Family Life Survey (IFLS-5), a national cross-sectional population-based survey among respondents with DM aged ≥15 years. DM status was confirmed by HbA1c testing, while sociodemographic and other health-related information was obtained from self-reported data. Gender, age, educational level, marital status, economic status, comorbidity, religiosity, residence and health insurance status were considered sociodemographic, whereas blood glucose monitoring status, sleeping problems, depression status, having a general medical check-up, satisfaction with healthcare needs and happiness status were considered behavioural risk factors. Awareness of DM medication was determined by self-reported responses to the question asked by the surveyor. Logistic regression analysis was used to evaluate the association between sociodemographic and behavioural factors and low awareness of DM medication. Odds ratios (ORs) with 95% confidence intervals (CIs) were reported. Result Most of the 706 respondents were female (58.8%) and aged 55–65 years (28.8%). Most of them showed low awareness of diabetes medication (87.7%). Irregular blood glucose monitoring (OR: 23.61, 95% CI 11.46–48.65; p < 0.001), without any comorbidity (OR: 2.03, 95% CI 1.05–3.90; p = 0.034), never had any general medical check-up (OR: 2.52, 95% CI 1.12–5.36; p = 0.016), 26–35 years of age (OR: 4.96, 95% CI 1.06–23.19; p = 0.042), 36–45 years of age (OR: 5.04, 95% CI 1.17–21.69; p = 0.030) and having no health insurance coverage (OR: 2.08, 95% CI 1.12–3.87; p = 0.021) were significantly associated with low awareness of diabetes medication. Conclusion Healthcare professionals should regularly evaluate blood glucose level, perform routine medical check-ups, prioritise patient satisfaction by providing appropriate care, involve patients in decision-making by determining their needs and then tailor an intervention to meet the need for, and improve their awareness of, DM medication.